Prognostic Score for Assessing the Risk of Incisional Ventral Hernias Strangulation - B. V. Sigua; V. P. Zemlyanoy; A. A. Kozobin; D. S. Semin (Неотложная медицинская помощь, 2022)
The problem of treatment for strangulated incisional hernia does not lose its relevance due to the large number of postoperative complications and high mortality rates, which significantly exceed these indicators in selective surgery. One of the solutions to this problem is to identify patients with a high risk of strangulation, which will allow you to perform the operation in a timely manner and avoid possible complications. The most relevant issue is the timing of surgery in patients with postoperative hernias after strangulation.